2007
DOI: 10.3892/ijo.31.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA against PTTG: A novel therapy for ovarian cancer

Abstract: Abstract. Ovarian epithelial cancer is a significant cause of death among women, accounting for 5% of all female cancer-related fatalities. A lack of reliable detection methods and resistance to chemotherapy agents are considerable obstacles in the treatment of this cancer. Recently, high-level expression of the pituitary tumor transforming gene (PTTG) was found in a wide range of tumors, including ovarian cancers. Elevated PTTG levels were found to induce cellular transformation in vitro and tumor formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Many research groups demonstrate a functional interfering RNA pathway in ovarian adenocarcinoma cell lines by using small interfering RNA constructs targeting mRNAs. 55,56 In addition, global microRNA profiling has showed that Drosha overexpression in cervical squamous cell carcinoma appears to be of functional significance. 57 However, despite evidence for decreased Dicer levels leading to a decrease in microRNA let -7, 7 no definitive evidence linking global alterations in microRNA profiles to Dicer levels has been demonstrated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups demonstrate a functional interfering RNA pathway in ovarian adenocarcinoma cell lines by using small interfering RNA constructs targeting mRNAs. 55,56 In addition, global microRNA profiling has showed that Drosha overexpression in cervical squamous cell carcinoma appears to be of functional significance. 57 However, despite evidence for decreased Dicer levels leading to a decrease in microRNA let -7, 7 no definitive evidence linking global alterations in microRNA profiles to Dicer levels has been demonstrated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PTTG1 enhances the cell proliferation, migration, invasion, and/or tumorigenicity and the induction of aneuploidy of cells derived from cancers of the human pituitary, kidney, esophagus, breast, head, and neck, liver, thyroid, lung, etc (Solbach et al, 2004;Zhou et al, 2005;Kim et al, 2006;Malik and Kakar, 2006;Rehfeld et al, 2006;Solbach et al, 2006;Wuttig et al, 2009;Liang et al, 2011). PTTG1 overexpression correlates with metastasis and poor overall survival in various human cancers (Heaney et al, 2000;Malik and Kakar, 2006;Wuttig et al, 2009), and decreasing PTTG expression through PTTG siRNA inhibits tumor growth in ovarian (El-Naggar et al, 2007), hepatic (Cho-Rok et al, 2006). And lung cancer cell lines, indicating that PTTG1 may be a new therapeutic target for cancer treatment.…”
Section: 3083 Pituitary Tumor Transforming Gene 1 Is An Independent mentioning
confidence: 99%
“…This study showed that by using the MISIIR promoter, 3 different tissues could be targeted: OSE, granulosa cells, and pituitary. However, possibly due to the weak expression of PTTG, the animals failed to generate any visible tumors, as the amount of expression is critical in ectopic tumor progression [116].…”
Section: Pttg Transgenic Micementioning
confidence: 99%
“…As PTTG has also been indentified in ovarian cancer taken from patients at the time of surgical resectioning [116], we wanted to identify the in vivo tumorigenic potential of PTTG through the development of a transgenic mouse model that could faithfully represent spontaneous EOC found in patients through the strong, non-specific overexpression of PTTG using the CMV promoter.…”
Section: Chapter 2 Pttg Transgenic Mice As a Model For Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation